KERAJINAN TANGAN HERBARIUM DI DESA PULAU SEMAMBU KECAMATAN INDERALAYA KABUPATEN OGAN ILIR - Marieska Verawaty (Aptekmas Jurnal Pengabdian pada Masyarakat, 2019)
Activity of Community service (PPM) as part of The Tri Dharma Perguruan Tinggi has been done on October 2015. The activity was about "The development of women’s creativity on production of various handicrafts made from flowers and dried plants by herbarium techniques” and was conducted on Semambu Island Village that is located on The North Indralaya District, Ogan Ilir Regency. This activity was in line with the home scale creative business development program of Sriwijaya University as an effort to improve the family income through the formation, fostering and assistance of small and medium-sized businesses, this activity is primarily targeted house-wives and young women in rural areas as an effort to support their family economy. Empowerment activities in this area are expected to have a positive impact on the development of creativity with economic value that also contained some of education, research and community service values. The activities were done by demonstration of making herbarium and handicrafts, and then it was followed by monitoring and evaluation. The utilisation of plants, flowers, and leaves for producing more high-value and economical handicrafts products by the herbarium can increase the community income and welfare.